Blockchain Ecosystem for Credit Transfer in Education. (9th December 2021) - Manoj, R.; Joshi, Sandeep; Dabholkar, Utkarsh; Prakash Panicker, Ganesh; Peter Kuriakose, Kevin; Zaguia, Atef; Monirujjaman Khan, Mohammad
Abstract : Data is the key to measuring educational effectiveness promptly. But data and education are trapped and siloed across centralized systems, causing information discrepancies and inaccuracies. This has caused countless delayed opportunities, academic credential disagreements, and never-ending confusion around learning potency. This lack of transparency, despite having its fair share of usefulness, has also been quite burdensome. To alleviate this issue, our team has developed a blockchain protocol that verifies professional certifications that have been earned both locally and through another well-established online educational portal. This system allows accuracy, reliability, and immutability that has never been implemented. This foundation of clear, verified data will then be used further to power blockchain-based applications. The result is that our attempt at a versatile, holistic, and decentralized view of educational performance ensures the best e-learning outcome for students and teachers alike.